Tourism–growth nexus under duress - Dibeh, Ghassan (2019)
The Syrian crisis that started in 2011 is considered by many to have affected negatively the Lebanese economy. A possible transmission channel from the crisis to the economy of Lebanon is tourism. This article investigates the tourism–growth nexus in Lebanon controlling for the instability caused by the Syrian crisis. We use a vector autoregression model with five monthly macroeconomic variables: a novel index for income, number of tourist arrivals, number of Syrian refugees, and casualties in both Lebanon and Syria during the conflict. The results show that the Lebanese economy was resilient to the political instability engendered by the Syrian crisis. The findings support both the tourism-led growth hypothesis and the ancillary growth-led tourism hypothesis. The article concludes that the tourism sector in Lebanon is robust to the political instability engendered by the Syrian crisis.